ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN PEKERJA PADA KAWASAN AGROWISATA DI KABUPATEN GIANYAR - Putu Ayu Pramitha Purwanti, Pande Made Witari Widiningsih, (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 2 (2020): VOL 9 NO 2, FEBRUARI 2020 [ 233 - 472 ], 2020)
Gianyar Regency is one of the regencies in Bali which is also famous as one of the tourist destinations by developing agrotourism potential. Agrotourism development will certainly have an impact on increasing employment, which is closely related to the income of the agro-worker. The level of income these workers can be influenced by education, employment status, tourist visits, the outpouring of working hours, and the tourism serviced. The purpose of this study was to examine the effect of education, employment status, tourist visits, agrotourism services, and outpouring of working hours on the level of income workers in agrotourism areas. The sample in this study was workers in agrotourism areas in Gianyar Regency based on their employment status. This sampling uses nonprobability sampling with purposive sampling technique. Data collection is done by the method of observation, interviews, in-depth interviews, and questionnaires. The data analysis technique used is multiple linear regression. The results of the analysis show that education, employment status, tourist visits, amd outpouring of work hpurs have a positive effect on the level of income of workers in agrotorism areas in Gianyar Regency. However, agrotourism services do not affect the level of income of workers in agrotourism areas.